Simulation of dual bondhead wirebonder - Chan, Lap Chi. (2008)
The concept of miniaturisation and productivity improvement induces a study on the conceptual design of a dual bondhead wirebonder; that is, adding an additional bondhead to the current single bondhead design. The main objective of the study is to determine the optimal operation mode (jobs sharing sequence of two bondheads), using analytical and simulation models. This is achieved in model experimentation. This study begins with a review and discussion of the concepts of model classification, modelling methods and modelling approaches. These concepts form the foundation for proper definition of problem and implementation. Detail implementation consists of problem formulation, model development and model verification.